2011
DOI: 10.1016/j.marenvres.2011.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Biological responses to contaminants in the Humber Estuary: Disentangling complex relationships

Abstract: Due to the ecological importance of estuaries, it is necessary to understand the biological effects that potentially toxic contaminants induce in bioindicator species. A key aspect is whether effects at lower levels of biological organisation transfer through the system to higher levels. In understanding such processes, characterising multivariate relationships between contaminants, sediment toxicities and detoxification processes are important. Worms (Hediste diversicolor) and sediments were collected along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Arguably, the system complexity enabled the absorption of these changes which did not follow through to higher levels of biological organization (i.e. environmental homeostasis; Elliott and Quintino, 2007;García-Alonso et al, 2011). Nonetheless, higher juvenile densities were not concordant with higher contribution to coastal adult populations.…”
Section: Multiple Indicators Of Habitat Qualitymentioning
confidence: 98%
“…Arguably, the system complexity enabled the absorption of these changes which did not follow through to higher levels of biological organization (i.e. environmental homeostasis; Elliott and Quintino, 2007;García-Alonso et al, 2011). Nonetheless, higher juvenile densities were not concordant with higher contribution to coastal adult populations.…”
Section: Multiple Indicators Of Habitat Qualitymentioning
confidence: 98%
“…All these chemicals can affect the natural condition of the faunal community. In estuaries, their presence has been associated with high sediment toxicities (GARCÍA-ALONSO et al, 2011). PCBs have been used as a flame retardant in plastics, while organochlorine pesticides are widely disseminated in natural environments after use for pest control (COMBI et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, these areas would be stressful only for marine or freshwater-adapted organisms, while for estuarine organisms the naturally occurring stress would be a positive state. It has been shown that natural stress in estuaries gives similar conditions to those found in anthropogenic stress, therefore the assessment of ecosystem structural features when looking for quality indicators makes the detection of the anthropogenic stress more difficult (Elliott and Quintino, 2007;García-Alonso et al 2011). Sun et al (2012) analyzed sediments from estuarine sites heavily modified and relatively unmodified and found shifts in both bacterial community composition and diversity by ARISA, a technique that allows analyzing bacterial communities to species level (Ramette, 2009).…”
Section: Introductionmentioning
confidence: 99%